Understanding quaternary compound Cu2ZnSnSe4 synthesis by microscopic scale analyses at an identical location. Issue 21 (12th May 2016) - Crossay, A.; Colombara, D.; Melchiorre, M.; Guennou, M.; Mendis, B. G.; Dale, P. J.
Abstract : Mapping of an identical location before and after chemical reactions reveals new insights on the synthesis of multinary compound films. For the photovoltaic material Cu2 ZnSnSe4, the detrimental ZnSe phase appears mainly on areas that were Zn poor before selenization. Abstract : The synthesis of multinary compound films from layered precursors is only partially understood. Identical location microscopy resolves the multi-step synthesis of Cu2 ZnSnSe4 from metallic stacks on the micron-scale. Large scale metal alloying and the seemingly illogical observation that ZnSe segregates preferentially on locations previously poor of zinc are revealed.